HUMAN HEALTH RISK ASSESSMENT OF HEAVY METALS IN Cynothrissa mento (REGAN, 1917) FROM BADAGRY CREEK, SOUTH-WEST, NIGERIA - NDIMELE, P.E; OWODEINDE, F.G. (Nigerian Journal of Fisheries, 2019)
This study was conducted to assess the potential impacts of consuming Cynothrissa mento from Badagry Creek, which is part of the Lagos Lagoon Complex that receives effluents from industries around Lagos. Water, sediment and fish (C. mento) samples were collected monthly for ten consecutive months (January – October, 2018) from four sampling stations in Badagry Creek. Water quality variables and heavy metal (Zn, Pb, Cu, Fe, Cr and Cd) content of water, sediment and C. mento were determined using standard procedures. Enrichment factor (EF) varied from 1.86x10-6 in Cr to 0.01 in Cd. Geoaccumulation index (Igeo) and contamination factor (CF) followed the trend with the highest values (Igeo = 6.33; CF = 120.97) obtained in Fe while the lowest values (Igeo = - 12.7; CF = 2.25x10-4 ) were recorded in Cr. The estimated daily intake (EDI) ranged from 4.79x10-6 mgkg-1day-1 in Cr to 5.4x10-3 mgkg-1day-1 in Fe. The lowest target hazard quotient (THQ) (1.65x10-5 ) was recorded in Cr while the highest (4.94x10-2 ) was obtained in Cd. The results show that Badagry Creek has low contamination and the consumption of C.mento does not constitute health risk to the consumers.